1998
DOI: 10.1046/j.1471-4159.1998.70010252.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐ and Region‐Specific Variations in Somatostatin Release Following Amygdala Kindling in the Rat

Abstract: Somatostatin biosynthesis is activated during and following kindling epileptogenesis. The aim of this study was to investigate whether this phenomenon translates into enhanced release of the peptide and whether it is involved in kindling maintenance. A marked increase in somatostatin-like immunoreactivity (somatostatin-LI) was observed in hilar interneurons of the hippocampus and in their presumed projections to the outer molecular layer 1 week, but not 1 month, after the last kindled seizure. No overt changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…In the current report, the increase of GAD 65 -IR, as well as CCK-IR, puncta detected 96 h after picrotoxin infusion is likely to reflect slowly evolving changes within hippocampal circuitry. Similar delayed effects have been shown using other experimental paradigms (e.g., Schwarzer and Sperk, 1995;Zhang et al, 1996;Simonato et al, 1998;Bouilleret et al, 2000). An increase in GAD 65 -and CCK-IR terminals could be parsimoniously explained by a direct and sustained increase of activation of intrinsic GABAergic neurons in the hippocampus by amygdalar afferents that results in a sprouting and/or increased size of GABAergic terminals.…”
Section: Changes In Terminalssupporting
confidence: 74%
“…In the current report, the increase of GAD 65 -IR, as well as CCK-IR, puncta detected 96 h after picrotoxin infusion is likely to reflect slowly evolving changes within hippocampal circuitry. Similar delayed effects have been shown using other experimental paradigms (e.g., Schwarzer and Sperk, 1995;Zhang et al, 1996;Simonato et al, 1998;Bouilleret et al, 2000). An increase in GAD 65 -and CCK-IR terminals could be parsimoniously explained by a direct and sustained increase of activation of intrinsic GABAergic neurons in the hippocampus by amygdalar afferents that results in a sprouting and/or increased size of GABAergic terminals.…”
Section: Changes In Terminalssupporting
confidence: 74%
“…Interestingly, as discussed above for the basal release, in vivo (present study) and slice (Vezzani et al, 1992) studies show greater somatostatin‐LI stimulation‐evoked release in the kindled than the control hippocampus; this, however, does not apply to isolated terminals (synaptosomes; Simonato et al, 1998). Again, the involvement of transsynaptic excitatory effects (lost in the synaptosomal preparation) may explain this discrepancy, and glutamate, because of the reasons discussed above and because it is phasically released during seizures (During and Spencer, 1993), is likely to play a leading role.…”
Section: Discussionsupporting
confidence: 47%
“…One interesting finding of this study is that basal (spontaneous) somatostatin‐LI release in the hippocampus is highly increased in kindled rats. Thus, in the kindled, as compared with control, hippocampus, somatostatin‐LI spontaneous release is increased by approximately twofold both in vivo (present study) and in slices (Vezzani et al, 1992) but not in isolated terminals (synaptosomes; Simonato et al, 1998). Furthermore, in the kindled hippocampus, somatostatin‐LI and preprosomatostatin mRNA levels are increased in the interneurons of the polymorphic cell layer of the hilus and of the stratum oriens of CA1 (Bendotti et al, 1993; Schwarzer et al, 1996); somatostatin‐LI content in tissue homogenates is also significantly increased (Vezzani et al, 1992); and at the level of the nerve terminals, somatostatin‐LI levels are elevated in a subset of fibers (Wanscher et al, 1990; Schwarzer et al, 1995, 1996) but not in all somatostatinergic terminals, as indicated by the lack of significant changes in synaptosomes isolated from the whole hippocampus (Simonato et al, 1998).…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations